Finite frequency range iterative learning fault-tolerant control for discrete time-delay uncertain systems with actuator faults. (December 2019) - Tao, Hongfeng; Paszke, Wojciech; Rogers, Eric; Yang, Huizhong; Gałkowski, Krzysztof
Abstract: The subject area considered is discrete linear time delay systems operating repetitively on a finite time interval with actuator faults, where the system resets at the end of each operation. Regulation of the dynamics is by iterative learning control and performance goals imposed over finite frequency intervals for the case of uncertainty in the dynamic model. To derive the results, the generalized Kalman–Yakubovich–Popov lemma is used. A simulation based case study is also given to demonstrate the applicability of the new results. Highlights: A class of discrete linear time-delay systems is considered. Iterative learning fault-tolerant control schemes are developed. Performance specifications in finite frequency domain are imposed. Monotonic error convergence conditions for the controlled ILC dynamics are derived. Robust control issue against structured uncertainty is solved. Both state and output feedback based designs are developed.